Beyond Censorship: Polish Independent Press Debates on Claude Lanzmann's Shoah. Issue 2 (May 2022) - Grądzka-Rejak, Martyna; Olaszek, Jan
The article analyzes discussions around the documentary film Shoah, by Claude Lanzmann, conducted in the uncensored press in communist Poland. In the literature on the subject, a popular thesis claims that the democratic opposition in Poland, like the authorities of the Polish People's Republic, subjected this film to explicit criticism. The authors' research into discussions about the Holocaust in the Polish independent press leads to the opposite conclusion. Ours analysis shows that authors publishing in the underground press had varied reactions to Lanzmann's film. Voices opposing the official campaign against the director and his film predominate (which did not mean a complete lack of criticism vis-à-vis some of the movie's features). We found only two opinions that can be considered clearly negative. The debate about Lanzmann's film is important because it shows the complexity of the democratic opposition's attitude of toward Polish-Jewish history and memory. In the opposition elite's view of history, two currents ran in parallel, often in statements authored by the same people. On the one hand, the trend was primarily affirmative, as a reaction to the communist propaganda that bypassed or completely distorted some aspects of Polish history. On the other hand, there was also a tendency to include more controversial or even clearly shameful aspects of the history of Poland.